2019
DOI: 10.9745/ghsp-d-19-00128
|View full text |Cite
|
Sign up to set email alerts
|

Postabortion Care and the Voluntary Family Planning Component: Expanding Contraceptive Choices and Service Options

Abstract: Universal access to voluntary postabortion family planning is a critical and compelling component of postabortion care. Such access should be joined with postpartum family planning services in national programs, health information systems, and training programs. The same providers and facilities deliver both services, and integration could yield cost efficiencies and increased coverage for women receiving postabortion care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Globally, comprehensive post-abortion family planning services have been endorsed as a high-impact practice in family planning services [89]. Several studies found that providing family planning services as part of postabortion care can increase contraceptive use and reduce repeat abortions [89,90]. Interestingly, our review suggested that comprehensive school support programs (provision of tuition fees, uniforms, and helpers to adolescents) to decrease school dropout rates, are not effective for reducing teenage pregnancy.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Globally, comprehensive post-abortion family planning services have been endorsed as a high-impact practice in family planning services [89]. Several studies found that providing family planning services as part of postabortion care can increase contraceptive use and reduce repeat abortions [89,90]. Interestingly, our review suggested that comprehensive school support programs (provision of tuition fees, uniforms, and helpers to adolescents) to decrease school dropout rates, are not effective for reducing teenage pregnancy.…”
Section: Discussionmentioning
confidence: 87%
“…Comprehensive training of abortion service providers and counseling of both partners on contraceptive methods can be effective for reducing unwanted pregnancy and unsafe abortion. Globally, comprehensive post-abortion family planning services have been endorsed as a high-impact practice in family planning services [89]. Several studies found that providing family planning services as part of postabortion care can increase contraceptive use and reduce repeat abortions [89,90].…”
Section: Discussionmentioning
confidence: 99%
“…111 In many settings, women do not receive contraceptive counseling after an abortion, and reasons include lack of trained staff, heavy workloads among providers, stockouts of methods and providers' lack of knowledge about how long it takes for fertility to return. 93,99,116,117 need for and use of services for which we have age-specific data, either from country surveys or model-based estimates. For other estimates (e.g., the cost of services), the underlying data are not age-specific but are based on rates or costs pertaining to all women of reproductive age.…”
Section: 2mentioning
confidence: 99%
“…These issues are the main causes of this contraceptive failure, and they lack ongoing guidance to acquire accurate and standardized knowledge of contraception and abortion [ 38 ]. However, because traditional health education is rather general, the health education method is not pertinence enough, and it is challenging to make patients have a deeper understanding of the disease under a single oral education, even though up to this point, the standardized PAC service provided by family planning workers has benefited many women [ 2 4 , 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since then, PAC has been implemented and studied in many parts of the world, and some results have been achieved. A large number of women who have been consulted by PAC have benefited [ 2 4 ]. PAC has also been widely promoted and implemented in China, and our family planning team has been working since 2011 to provide PAC services to women with unintended pregnancies, encouraging the implementation of highly effective contraceptive measures to reduce the harm caused by further unintended pregnancies and repeated miscarriages.…”
Section: Introductionmentioning
confidence: 99%